Overload in caregivers of aphasic individuals in speech-language therapy (Revista Contexto & Saúde, 2023)
In this research, the objective was to analyze the burden in terms of social, emotional/subjective and physical aspects for caregivers of subjects with aphasia in speech-language therapy. Participants answered the instrument on questions related to aphasia, as well as the Zarit overload protocol. There was a prevalence of female caregivers, all family members, that is, informal caregivers. Questions related to speech production and comprehension were the ones with the greatest impact for caregivers. As for physical and emotional overload, there were moderate to severe levels for most of these caregivers. It is important to pay attention to such physical and emotional overloads to which the caregiver is exposed, since they interfere significantly in the rehabilitation process of individuals with aphasia.
Keywords: Aphasia; Caregivers; Communication Barriers; Quality of Life; Speech, Language and Hearing Sciences